Claude Monet - Nunhead, Nancy; Monet, Claude 1840-1926. (Greenwich, CT Barnes & Noble, Inc., 1994)
Examines the life and work of Monet, describing his struggle for artistic recognition and providing examples of his paintings.
Keywords: Monet, Claude -- 1840-1926.